An innovation bootcamp model for developing youth-led HIV self-testing delivery strategies in Nigeria: post-designathon capacity building - Nwaozuru, Ucheoma; Obiezu-Umeh, Chisom; Tahlil, Kadija M.; Gbaja-Biamila, Titilola; BeLue, Rhonda; Idigbe, Ifeoma; Oladele, David; Conserve, Donaldson; Airhihenbuwa, Collins; Xian, Hong; Musa, Adesola Z.; Olusanya, Olufunto; et al. (Frontiers in Public Health, 2024)
IntroductionMany designathons, hackathons, and similar participatory events suffer from minimal training and support after the events. Responding to this need, we organized a health innovation bootcamp: an intensive, team-based apprenticeship training with research and entrepreneurial rigor among young people in Nigeria to develop HIV self-testing (HIVST) delivery strategies for Nigerian youth. The purpose of this paper was to describe an innovation bootcamp that aimed to develop HIVST delivery strategies for Nigerian youth.MethodsThe four-week, in-person innovation bootcamp, informed by youth participatory action research and comprised a series of workshops, took place in Lagos, Nigeria. The goal was to build research and entrepreneurial capacities among young people to develop and implement HIVST strategies. A qualitative content analysis informed by an adapted World Health Organization’s HIVST delivery framework explored key elements of the proposed HIVST service delivery strategies developed at the bootcamp.ResultsTwenty participants, aged 18–24 years, from five teams completed the innovation bootcamp. The five teams developed HIV service delivery strategies that included an element of repacking HIVST kits to make them more appealing to young people. Other strategies that emerged included leveraging community engagement platforms (e.g., vocational skills training and youth community events) to promote HIVST, and the use of reward-referral system to encourage HIVST uptake among young people. All strategies included ways to ensure privacy protection for recipients of the HIVST delivery package.ConclusionThis study demonstrated the feasibility and acceptability of the health innovation bootcamp model to create HIVST designed for and led by young people. This suggests a way to build capacity after participatory events to sustain youth-led research, which could have implications for post-designathon training.